PERAN SOSIAL BANK SYARIAH BERDASARKAN INDEKS MAQASHID SYARIAH (STUDI KASUS DI JORDAN) - Sari, Kartika; Ismail, Munawar; Ekawaty, Marlina (FIA UB, 2019)
This study aims to determine the implementation of Islamic bank social values as they should have been implemented. This study uses the Maqashid Syariah Index with three main social indicators, namely education, justice, and social welfare. The object of this research are three Islamic banks in Jordan (Jordan Islamic Bank, Safwa, and International Islamic Arab Bank). The results showed that all the banks have a lowÂ Maqashid Syariah Index for all indicators, which meant that the practice of implementing the social values of Islamic banks in Jordan are not close to what people have expected especially for indicators of justice and social welfare. In the future, Islamic banks need to increase social contributions, especially on indicators of justice and social welfare.Â